Empowering Social Environment as Scaffolding for Students with Autistic Spectrum Disorder (ASD) in Teaching Basic Communication - Ni Nyoman Padmadewi; I Made Sukma Adisetiawan Sukadana; I Putu Yoga Purandina; Ida Ayu Fortuna Ningrum; Lesly Narwasti Ndun (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2024)
Students with ASD have obvious characteristics that they have limitations in making communication and have low social awareness. For that reason, they need to be supported on how they can improve their communication ability. This research aimed to describe how the social environment is empowered and created to help students with ASD learn to communicate. The study's design was a multi-case study conducted in an inclusive school in North Bali. Three cases of students with ASD with their teachers, the school principal, and a technical assistant were involved as the study's subjects. The data were collected for 12 months and analyzed qualitatively. The study results show that several types of social environments were modified to teach students about basic communications such as morning circles, cooperative buddy programs, sensory garden programs, modelling, and go-play activities. The use of the programs functions as scaffolding, which then indicates improvements in the students ' social interactions and basic communication. The implication of this study suggests the importance of creating a supportive social environment program for students with ASD to enhance their social awareness and interaction.Students with ASD have obvious characteristics that they have limitations in making communication and have low social awareness. For that reason, they need to be supported on how they can improve their communication ability. This research aimed to describe how the social environment is empowered and created to help students with ASD learn to communicate. The study's design was a multi-case study conducted in an inclusive school in North Bali. Three cases of students with ASD with their teachers, the school principal, and a technical assistant were involved as the study's subjects. The data were collected for 12 months and analyzed qualitatively. The study results show that several types of social environments were modified to teach students about basic communications such as morning circles, cooperative buddy programs, sensory garden programs, modelling, and go-play activities. The use of the programs functions as scaffolding, which then indicates improvements in the students ' social interactions and basic communication. The implication of this study suggests the importance of creating a supportive social environment program for students with ASD to enhance their social awareness and interaction.